Development of numerical model capturing cyclic behavior of Two-Side clamped infill plates. (June 2023) - Shin, Dong-Hyeon; Kim, Hyung-Joon
Abstract: This study aims to propose a simple numerical model methodology for two-side clamped infill steel plates with various aspect ratios, slenderness ratios and even different steel grades. The modeling element constructed using the methodology expects to be directly implemented into computer structural software for nonlinear time-history analyses of structures employing two-side clamped infill plates. The suggested model is constructed with their force–displacement relation including nonlinear and cyclic effects which can be defined by modeling parameters evaluated from empirical equations. The empirical equations are developed using regression analyses to agree with the parametric analysis results with detailed finite element models of two-side clamped infill plates. A proposed numerical model including the hysteretic characteristics was validated by comparison with existing experimental results conducted by other studies. It is confirmed to utilize the proposed numerical model that can accurately represent cyclic behavior over entire response ranges including buckling, tension field action representing the post-buckling behavior, and fracture of steel plates.